Analisis Penerapan Posisi Head Up 30 Derajat Pada Pasien Dengan Diagnosa Medis Intracerebral Hemorrahage Post Craniectomy Di RSUP. Prof. Dr. R .D Kandou Manado - Lumenta, Tesalonika; Mulyadi, Mulyadi; Bidjuni, Hendro Joli (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Background. Head injuries are a global problem and one of the leading causes of death and disability throughout the world. A head up position of 30 degrees can increase blood flow to the brain and prevent the occurrence of Intracranial Pressure (ICP). Method used is descriptive case study research. The case study was carried out on patients who were in the Irina A Lower Inpatient Room at RSUP. Prof. Dr. R.D Kandou Manado. This scientific work was carried out by providing nursing care applying a 30 degree head up position with MAP observation every 2 hours for 1 shift. Results of this case study found 4 nursing problems, namely decreased intracranial adaptive capacity, ineffective airway clearance, impaired tissue integrity and hyperthermia with The main problem is a decrease in intracranial adaptive capacity with the intervention of giving a head up position of 30 degrees for 3 days, implemented in patients and carried out by evaluation, it was found that the results of a decrease in ICP in patients through the observation results show that MAP decreased. Discussion. The 30 degree head up position is a position to raise the head from the bed at an angle of around 30 degrees and the body position is parallel. The author set the patient's head at 30 degrees with the aim of overcoming the nursing problem of decreased intracranial adaptive capacity by observing vital signs every 2 hours and analyzing changes in Mean Arterial Pressure (MAP). The reason Mean Arterial Pressure (MAP) was measured in this study was because of the unique clinical symptoms in head injury patients, namely decreased level of consciousness and changes in blood pressure. Conclusion is that the 30 degree head up position has an effect on reducing intracranial pressure in patients with moderate head injuries.